2018
DOI: 10.1007/s00417-018-4118-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic contact lenses vs. tight bandage patching and pain following pterygium excision: a prospective randomized controlled study

Abstract: The application of TCL in the first 24 h after pterygium surgery resulted in more discomfort and pain and decreased quality of sleep compared with tight bandage patching. Despite the limitation in monocular vision and the inconvenience of gauze bandages, they are preferred over TCL for alleviating pain following pterygium surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Despite the fact that bandage patching may interfere with visual field (thus contraindicated in case of monocular vision), it has been reported that this method procures better pain relief and sleep quality in the first 24 hours after pterygium excision when compared with TCLs. 162 For this reason, tight bandage patching should be preferred over contact lenses if no contraindications to ocular occlusion are observed. TCLs can still be applied in case of persistent pain or corneal defects after the first postoperative day.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…Despite the fact that bandage patching may interfere with visual field (thus contraindicated in case of monocular vision), it has been reported that this method procures better pain relief and sleep quality in the first 24 hours after pterygium excision when compared with TCLs. 162 For this reason, tight bandage patching should be preferred over contact lenses if no contraindications to ocular occlusion are observed. TCLs can still be applied in case of persistent pain or corneal defects after the first postoperative day.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…Pterygium is a common ocular surface disease, defined as fibrovascular overgrowth of the Tenon's capsule and bulbar conjunctiva onto the cornea. The incidence of pterygium ranges from 0.7% to 31% [1]. The exact pathogenesis of this injury is complex, and it is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the effects of BSCLs after pterygium surgery on reepithelialisation and pain in 39 eyes (20 eyes randomised to the BSCL group, 19 to the no lens control group) found BSCL use significantly reduced pain and enhanced epithelial healing [191]. In a prospective study, pain, discomfort, and sleep quality during the initial 24 h after pterygium surgery were compared between subjects using BSCLs versus subjects who were patching [192]. Interestingly, pain levels were worse and sleep quality was decreased in the BSCL group.…”
Section: Pterygium Surgerymentioning
confidence: 99%